PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN TEKNIK DI PT PLATINUM CERAMICS INDUSTRY SURABAYA - Nuzulul Fatimah (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2015)
The business world required creating high employee performance to the company's development. Companies must be able to build and improve performance in their environment. The purpose of this study was to identify and analyze the influence of leadership and compensation to employee performance in PT Platinum Ceramics Industry Surabaya.Tthe samples are 33 technical employees, while the test equipment used is the analysis techniques Linear regression with SPSS 14.0.The test result variable compensation and leadership significant influence on employee performance. And it turns out variable compensation of the most dominant influence on employee performance that is equal to 56.40%.